Two-Stage Optimization Model of Centralized Energy Storage Participating in Peak Shaving with Maximum Reserve Capacity and Minimum Carbon Emission of the System - Zhiyao Zhang; Jingjie Huang; Nianguang Zhou; Hongming Yang; Renjun Zhou (International Transactions on Electrical Energy Systems)
As the proportion of renewable energy increases in power systems, the need for peak shaving is increasing. The optimal operation of the battery energy storage system (BESS) can provide a resilient and low-carbon peak-shaving approach for the system. Therefore, a two-stage optimization model for grid-side BESS is proposed. First, the carbon emission model of thermal power units considering BESS is proposed to describe the ability of the BESS in reducing the carbon emissions. Second, in order to deal with the uncertainty of the photovoltaics and wind forecast errors, a certain capacity of BESS is reserved. The model in the first stage takes the lowest carbon emission of the system as the goal, and the model in the second stage determines the BESS reserve capacity with the objective of minimizing the risk cost of the system. The simulation results show that the carbon emission model of thermal power units with BESS can measure the contribution of energy storage to emission reduction. By setting the reserve capacity of energy storage, the peak-shaving resilience of the system is improved, and the risk of photovoltaics and wind forecast error is reduced.